Strategi Manajemen Krisis Kementrian Pariwisata RI dalam Menghadapi Krisis Kepariwisataan Akibat Tsunami Selat Sunda - Bayu Suriaatmaja Suwanda; Shania Aprilia Sari; Herry Rachmat Widjaja (Jurnal Sains Indonesia, 2020)
Being located on the Pacific Ring of Fire (an area with a high degree of tectonic activity), make Indonesia has to cope with the constant risk of Natural disasters. Natural disasters can cause a tourism crisis. The Tsunami in Sunda Strait that had a major impact on tourism activities, that make the ministry of tourism’s Public Communication Berau as public relations has an important role in handling the tourism crisis with good crisis management strategy. The report was to understand how the crisis management strategy of the Ministry of Tourism Public Relations in handling the tourism crisis due to the Sunda Strait Tsunami in the end 2018. The crisis management strategy in handling this crisis divided into three phase, namely the emergency response phase, the rehabilitation phase and the normalization phase. The crisis management strategy called “Selat Sunda Bangkit”.